Habit formation and labor supply - Helmuth Cremer; Philippe de Donder; Darío Maldonado; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper shows that the combination of habit formation - present consumption creating additional consumption needs in the future - and myopia may explain why some retirees are forced to unretire, i.e., unexpectedly return to work. It also shows that when myopia about habit formation leads to unretirement there is a case for government's intervention. In a first-best setting the optimal solution can be decentralized by a simple Pigouvian (paternalistic) consumption tax (along with suitable lump-sum taxes). In a second-best setting, when personalized lump-sum transfers are not available, consumption taxes may have conflicting paternalistic and redistributive effects. We study the design of consumption taxes in such a setting when myopic individuals differ in productivity.
Keywords: D91; H21; H55; 330; Habit formation; myopia; unretiring; Einkommenshypothese; Konsum; Risiko; Altersgrenze; Arbeitsangebot; Verbrauchsteuer; Theorie